Implementation of educational technology on antimicrobial resistance for health professionals in a teaching hospital - Study protocol (Research, Society and Development, 2025)
Antimicrobial resistance (AMR) has become a priority issue in the World Health Organization's global action plan and has been increasing worldwide, resulting in higher costs and negative clinical outcomes, especially in low- and middle-income countries. It is understood that preventive actions against AMR should have a multidisciplinary approach, identifying aspects related to patient safety culture. Educational actions promote understanding of how resistance develops and spreads, helping to understand the specificities of health services. Thus, this protocol proposes the development of an educational strategy to combat AMR. It is a quasi-experimental study protocol with the development of educational technology in e-health format, aimed at health professionals. The study will be conducted at a hospital located in Diamantina, Minas Gerais. The target audience will comprise a sample of professionals involved in direct and indirect care of patients admitted to the institution under study. The research will be conducted in the following phases: 1. Pre-development of the technology: characterization of the study population in terms of socio-demographic aspects and identification of educational needs related to the prevention of AMR; 2. Development and validation by judges: Phase of development and validation of content and phase of proposal of the technology. 3. Technology implementation phase: The aim is to provide an educational tool adapted to the linguistic and cultural level of the subgroups of health professionals and contribute to the fight against AMR; 4. Evaluation of the contributions of technology to changing the behavior of professionals.